PC-904, a New Semisynthetic Penicillin - Bodey, Gerald P. (1978)
Sodium 6{d(−)-α(4-hydroxyl-1,5 naphthyridine-3-carboxamido)phenylacetamido} penicillanate (PC-904) is a new semisynthetic penicillin with broad-spectrum activity against gram-positive cocci and gram-negative bacilli. At a concentration of 1.56 μg/ml, it inhibited 100% of isolates of Proteus mirabilis, 89% of Pseudomonas aeruginosa, 67% of Escherichia coli, and 45% of Enterobacter spp. At a concentration of 12.5 μg/ml, it inhibited 75% of Klebsiella spp. and 67% of Serratia marcescens. PC-904 failed to inhibit the growth of gram-negative bacilli when large inocula were used. Some differences were noted when organisms were tested in different media or at different hydrogen ion concentrations. It is more active than mezlocillin, azlocillin, ticarcillin, carbenicillin, and amoxicillin against E. coli, Klebsiella spp., and P. aeruginosa.